2000
DOI: 10.1001/jama.284.16.2070
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Follow-up Care and Life-Threatening Illnesses Among High-Risk Infants

Abstract: Comprehensive follow-up care by experienced caregivers can be highly effective in reducing life-threatening illness without increasing costs among high-risk inner-city infants. JAMA. 2000;284:2070-2076.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 27 publications
(29 reference statements)
0
66
0
Order By: Relevance
“…13 Structured post-NICU discharge follow-up care can substantially save net healthcare costs by safely facilitating earlier discharge from the NICU [14][15][16] and decreasing the incidence of lifethreatening illnesses and intensive care admissions in first year of life. 17 Follow-up clinics may not be directly profitable to the hospitals, but they help in substantially lowering the total healthcare costs related to prematurity. As the preterm and low birth weight rates continue to rise 18 and the survival rates of highrisk infants continues to improve, robust high-risk infant follow-up care programs become vital in decreasing the burden of prematurity-related healthcare costs.…”
Section: Discussionmentioning
confidence: 99%
“…13 Structured post-NICU discharge follow-up care can substantially save net healthcare costs by safely facilitating earlier discharge from the NICU [14][15][16] and decreasing the incidence of lifethreatening illnesses and intensive care admissions in first year of life. 17 Follow-up clinics may not be directly profitable to the hospitals, but they help in substantially lowering the total healthcare costs related to prematurity. As the preterm and low birth weight rates continue to rise 18 and the survival rates of highrisk infants continues to improve, robust high-risk infant follow-up care programs become vital in decreasing the burden of prematurity-related healthcare costs.…”
Section: Discussionmentioning
confidence: 99%
“…One center has reported a randomized trial of primary care for ELBW infants and has shown a decrease in readmissions to the pediatric intensive care unit, a decrease in intensive care days, and a reduction in cost of overall health care. 31 Other services provided at various centers include regular phone calls, periodic developmental assessments, and case management support. Therefore, the effects of racial disparities may have been blunted by the efforts of the investigators to include all infants regardless of race or ethnicity, primary care at some institutions, and the support services offered by all the followup programs.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] These rehospitalizations are accompanied by significant morbidity and sometimes mortality 4,5 and occur at high cost to the family as well as society. 4,6 Strategies such as the use of prophylaxis for respiratory syncytial virus infections 7 and comprehensive follow-up care 8 are designed to reduce these rehospitalizations. Few studies have evaluated models to predict which prematurely born infants will need rehospitalization or will have persistent respiratory problems after discharge from the hospital.…”
mentioning
confidence: 99%